Mortality of TB-HIV Co-Infection Patients Based on CD4 Level: Meta-Analysis - Victoria Husadani Permata Sari; Setyo Sri Rahardjo; Bhisma Murti (Indonesian Journal of Medicine, 2022)
Background:  Tuberculosis (TB) is the most common cause of death in patients with the Human Immunodeficiency Virus (HIV). Understanding CD4 as a predictor of mortality from TBHIV coinfection is critical to improving disease management and minimizing mortality. This study aims to examine the mortality risk of TBHIV-coinfected patients based on CD4 values.Subjects and Method:  Metaanalysis was performed according to the PRISMA flow chart and the PICO model (Population: TBHIV coinfected patients, Intervention: CD4 value <200 cells/µL, Comparison: CD4≥200 cells/µL, Outcome: mortality). The databases used are Google Scholar, PubMed, Scopus, Proquest, and Science Direct. Keywords used (coinfection OR "mixed infection") AND (HIV OR "Human Immunodeficiency Virus") AND (TB OR “tuberculosis”) AND ("CD4 count" OR "T4 lymphocyte") AND “mortality”. The inclusion criteria were full-text articles with cohort studies published in 20122022, articles in English, and multivariate analysis using the adjusted hazard ratio. Analysis was performed with Revman 5.3.Results:  17 articles with cohort design originating from Ethiopia, Khayelitsha, Kenya, Cape Town, Uganda, Brazil, Suriname, Sao Paulo, Guinea Bissau, Myanmar, Durban, Ireland, China, and multicountry studies between Europe and Latin America totaling 24,514 research sample. A meta-analysis of 10 study cohorts concluded that CD4<200 cells/µL had a 2.00 times risk of mortality compared with CD4 values ≥200 cells/µL (aHR=2.00; 95% CI 1.44 to 2.78; p<0.001). A meta-analysis of 7 study cohorts concluded that CD4<100 cells/µL had a 2.40 time risk of mortality compared with CD4 values≥200 cells/µL (aHR=2.40; 95% CI 1.61 to 3.57; p<0.001). A meta-analysis of 7 study cohorts concluded that CD4<50 cells/µL had a 3.12 times risk of mortality compared with CD4 values≥200 cells/μL (aHR=3.12; 95% CI 1.51 to 6.46; p<0.001).Conclusion:  Decreased CD4 values increase the risk of mortality.Keywords:  tuberculosis, HIV, CD4, mortality, meta-analysisCorrespondence: Victoria Husadani Permata Sari. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir Sutami 36A, Surakarta 57126, Jawa Tengah. Email: victoriahusadani@gmail.com. Mobile: 081393539020.Indonesian Journal of Medicine (2022), 07(04): 456470https://doi.org/10.26911/theijmed.2022.07.04.11